A Pilot Study: Bed Exercise with “Pun Ngai” in Pre-and Stage-1 Hypertensive Patients - Chanavirut, Raoyrin; Wongsaenchoom, Phuttaraphong; Sukboonthong, Waraporn; Chuailek, Tapanee; Donpunha, Wanida; Yonglitthipagon, Ponlapat; Nakmareong, Saowanee (Archives of Allied Health Sciences, 2019)
The aim of this cross-over design study was to assess the response of heart rate (HR), blood pressure, oxygen saturation, rating of perceived exertion (RPE), rating of perceived dyspnea (RPD) and the opinion for using “Pun Ngai”, a modified bicycle. Twenty-five pre-and stage-1 hypertensive participants were recruited to the study. They performed randomly either graded cycle exercise or resting on the bed in which the washout period between the sessions was 1 day apart. In the beginning, muscles around the lower back, buttock and posterior thigh were stretched. Then, the participants were asked for cycling or resting in bed at 30 degrees head upright position for 20 minutes. For cycling, the exercise began with 3 minutes free load warm up with 40 RPM, then, performed 5-min incremental load in each step for three steps and finished with 2 minutes free load for cool down. The outcome parameters were assessed at baseline, before three steps of the speed was increased and after finish the experiment. After that, the participants were required to complete the questionnaire. The results showed that, for cycling, HR and systolic blood pressure (SBP) increased significantly (p<0.05) when compared with the rest period and increased significantly (p<0.05) between the group at the maximal work load. In contrast, diastolic blood pressure (DBP), mean arterial pressure (MAP), oxygen saturation, RPD and RPE did not change when compared both within and between the groups. Additionally, the opinion from questionnaire indicated that the participants satisfied the general appearance of the equipment in which some details should be added for maximize the equipment efficiency. Based on the result, it can be concluded that exercise with “Pun Ngai” increases significantly of HR and SBP while another parameter did not change. In addition, some of the equipment details should be modified.